PERSEPSI KUALITAS PRODUK, BRAND AWARENESS DAN CELEBRITY ENDORSEMENT TERHADAP MINAT BELI OPPO SMARTPHONE PADA MAHASISWA FAKULTAS EKONOMI UNIBA SURAKARTA - Ayu Intan Pratiwi; Bambang Mursito; Eny Kustiyah (JURNAL ILMIAH EDUNOMIKA, 2020)
This study aims to determine the effect of Product Quality, Brand Awareness and Celebrity Endorsement on the Opposition of Buying Oppo Smartphones on Students of the Faculty of Economics, UNIBA Surakarta. This type of research uses quantitative methods, the population taken in this study were students of Surakarta Samples used in this study were 80 people sampling techniques using Convenience sampling techniques. Data analysis techniques in this study used multiple Linear analysis techniques. F test results state that Product Quality, Brand Awarenesss and Celebrity Endorsement simultaneously and significantly influence the Oppo Smartphone Interest in the Faculty of Economics, UNIBA Surakarta. while based on the t test stated that partially the quality of the product had a positive significant effect on the Purchase Oppo Smartphone Interest in the Faculty of Economics UNIBA Surakarta. Brand Awareness partially influences positively and significantly the interest in buying Oppo Smartphones in UNIBA Surakarta Faculty of Economics Students. Celebrity Endorsement partially has a positive and significant influence on the Oppo Smartphone Interest in UNIBA Surakarta Faculty of Economics Students. Keywords: Product quality, Brand Awarenesss,, Celebrity Endorsement, Purchase interest.